IMMOBILIZATION OF HUMIC ACID ON CHITOSAN USING PROTECTED CROSS-LINKING REACTION METHOD AND ITS APPLICATION AS SORBENT FOR Pb(II), Cd(II), AND Cr(III) - Uripto Trisno Santoso; Dewi Umaningrum; Utami Irawati; Radna Nurmasari (Indonesian Journal of Chemistry, 2008)
Immobilization of humic acid (HA) on chitosan has been done by using a protected cross-linking reaction method and the product was then utilized as sorbent for Pb(II), Cd(II), and Cr(III). HA was cross-linked with chitosan by using glutaraldehyde in order to obtain sorbent insoluble in aqueous acidic and basic solution. Protection of the active sites of HA was carried out by interacting HA with Pb(II) before performing the cross-lingking reaction in order to maintain its adsorption capacity The result showed that the amount of immobilized HA on chitosan was 99.7% by weight. The solubility of the immobilized HA were < 0.5% at pH 6 and < 1.0% at pH 12. The amount of immobilized HA and its solubility indicated that the protection pretreatment did not interfere the cross-linking reaction between HA and chitosan. The adsorption capacity of the sorbent for Pb(II), Cd(II), and Cr(III) were 416.7 mg/g, 332.3 mg/g, dan 714.3 mg/g, respectively.